Odpowiedzi

2009-12-09T19:13:31+01:00
A){3x=12
{x-y=1

3x = 13 |:3
x = 4

x - y = 1
4 - y = 1
y = 3

b){5y=2
{x=y=2⅖

5y = 2 |:5
y = ⅖

x + y = 2⅖
x + ⅖ = 2⅖
x = 2⅖ - ⅖
x = 2

c){4y-x=6
{17y=0

17y = 0 |:17
y = 0

4y - x = 6
-x = 6 |*(-1)
x = -6

d){a=b
{2a+b=9

a - b = 0
2a + b = 9

3a = 9 |:3
a = 3

a - b = 0
3 - b = 0
b = 3

e){u=4v
{5u-v=10

u - 4v = 0 |*(-5)
5u - v = 10

-5u + 4v = 0
5u - v = 10

3v = 10 |:3
v = 3⅓

5u - v = 10
5u = 10 + v
5u = 10⅓ |:5
u = 10 ⅓ * ⅕
u = 31/3 * 1/5 = 31/15 = 2 1/15
u = 2 1/15

f){3r=s
{3r+s=24

3r - s = 0
3r + s = 24

6r = 24 |:6
r = 4

3r - s = 0
3*4 - s = 0
-s = -12 |*(-1)
s = 12
6 2 6